Interaction Management Strategies in English Literature Lectures in Indonesian University Setting - Akhyar Rido; Heri Kuswoyo; Rameliya Ayu (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
Interaction management strategies are increasingly set to become a vital factor in fostering active participants in university lectures. Following Rido, Ibrahim & Nambiar’s (2015) framework, this study investigated interaction management strategies used in English literature lectures in a university setting in Indonesia. This study employed a qualitative method and the data were gathered through video recordings. The findings showed that all literature lecturers employed three kinds of interaction management strategies such as code strategies, emotional strategies, and managing strategies. In code strategies, the lecturers used English during the entire class for clarity in opening, explanation, example, and closing. Meanwhile, in emotional strategies, the lecturers shared common strategies namely using non-verbal gestures and using humours or jokes in order to invite participation, to increase student’s motivation, and to create conducive learning environment. Then, in terms of managing strategies, the lecturers decided topic, controlled or switched the topic of discussion, decided who speaks, gave direction or commanded the students, gave extended wait time, and offered opportunity for student to speak in order to enable the students express their ideas and engage with the lectures. It is hoped that insights gleamed from this study will assist such lecturers to successfully manage their lectures and navigate the distribution of participation as well as content of the lesson.